2009
DOI: 10.1063/1.3224730
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity of electron–hole pairs in a bilayer graphene system in a quantizing magnetic field

Abstract: The state with a spontaneous interlayer phase coherence in a graphene based bilayer quantum Hall system is studied. This state can be considered as a gas of superfluid electron-hole pairs with the components of the pair belonging to different layers. Superfluid flux of such pairs is equivalent to two electrical supercurrents in the layers. It is shown that the state with the interlayer phase coherence emerges in the graphene system if a certain imbalance of the Landau level filling factors of the layers is cre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Exciton condensation in graphene has attracted considerable theoretical attention (Abergel et al, 2013;Aleiner et al, 2007;Efimkin and Lozovik, 2011;Fil and Kravchenko, 2009;Efetov, 2008, 2010;Lozovik et al, 2012;Lozovik and Sokolik, 2008;Min et al, 2008;Pikalov and Fil, 2012;Sodemann et al, 2012;Suprunenko et al, 2012;Zhang and Joglekar, 2008). Several contradicting values of the transition temperature in double-layer graphene systems have been reported.…”
Section: B Interlayer Exciton Formationmentioning
confidence: 99%
“…Exciton condensation in graphene has attracted considerable theoretical attention (Abergel et al, 2013;Aleiner et al, 2007;Efimkin and Lozovik, 2011;Fil and Kravchenko, 2009;Efetov, 2008, 2010;Lozovik et al, 2012;Lozovik and Sokolik, 2008;Min et al, 2008;Pikalov and Fil, 2012;Sodemann et al, 2012;Suprunenko et al, 2012;Zhang and Joglekar, 2008). Several contradicting values of the transition temperature in double-layer graphene systems have been reported.…”
Section: B Interlayer Exciton Formationmentioning
confidence: 99%
“…At d > d c the collective mode frequency in a certain range of wave vectors becomes imaginary, that corresponds to instability of the state with pairing. The magnitude of d c grows with increasing the imbalance [18]. Increasing the imbalance leads to decreasing the superfluid density n s , i. e. the increase of d c can be linked to the decrease of n s .…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently a suggestion has been made to use graphene layers as components of bilayer systems [14][15][16][17][18]. Further investigations revealed that a serious problem in this case is screening of Coulomb interaction between the electron and the hole [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The critical density n v,c is proportional to ρ 2 s . It is known that the mean-field approximation overestimates the superfluid stiffness ρ s : it does not take into account quantum and thermal excitations, and the interaction with impurities that reduce the superfluid stiffness (see, for instance, [28][29][30]). Therefore, the actual critical density can be considerable smaller.…”
Section: Vortices In Exciton Superfluids In Quantum Hall Bilayersmentioning
confidence: 99%